2018
DOI: 10.30845/jesp.v5n4p25
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Demographic Factors and Adjustment to University for Mature-Age, Undergraduate Students

Abstract: It is important that all students who enrol in tertiary institutions can complete their chosen course. A smooth transition is critical in ensuring that the initial experience of university is positive and that students adjust well to the academic, social and personal demands of tertiary study. Some issues of adjustment affect all first-year students, while some are specific to certain demographic groups. Older students may have extra responsibilities and demands on their time, which can have a negative impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…According to this finding demographic factor such as gender is a significant predictors of academic adjustment (Wider et al, 2016). Another study discovered that adjusting for different demographic groups resulted in Significant, positive associations were found to the Social Adjustment, Personal Adjustment, and Attachment (Dawborn-Gundlach, 2018). The students reported that age played a significant role in college adjustment, as the older students seemed to be more experienced than the younger ones (Zhuhra & Mardiastuti, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…According to this finding demographic factor such as gender is a significant predictors of academic adjustment (Wider et al, 2016). Another study discovered that adjusting for different demographic groups resulted in Significant, positive associations were found to the Social Adjustment, Personal Adjustment, and Attachment (Dawborn-Gundlach, 2018). The students reported that age played a significant role in college adjustment, as the older students seemed to be more experienced than the younger ones (Zhuhra & Mardiastuti, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Preliminary data indicate that the pandemic situation and online learning have posed more significant challenges to the Class of 2021 students in the Psychology Faculty compared to those who experienced the first year before the pandemic. Their initial experiences in tertiary institutions can influence their attitudes and confidence towards their future studies (Dawborn-Gundlach & Margetts, 2018). Meanwhile, the Class of 2021 students will now enter their second year of study, which presents distinct challenges.…”
Section: Introductionmentioning
confidence: 99%